Analysis of major fragrant compounds from citrus grandis flowers extracts - Zarina Zakaria; Suhana Zakaria; Mohd Azlan Mohd Ishak (Universiti Kebangsaan Malaysia, 2010)
Various sampling techniques such as hydrodistillation, Soxhlet extraction and solid phase micro extraction (SPME) were used to extract compounds, i.e. the active components attributed to fragrance of C. grandis flowers. Gas chromatograph mass spectrometry was then used to identify and quantify the active components obtained from the techniques. The results thus far showed that, buds and blossoms of this flower which possesses a strong floral-, jasmine- and orange-like aroma contain β-myrcene, limonene, ocimene, linalool and caryophyllene as the major compounds. In hydrodistillation technique the levels of ocimene and linalool detected in blossom were higher than in the bud at 7.37 and 15.93%, respectively, while in the bud, limonene was the highest, i.e. 4.57%. In Soxhlet extraction, however the bud was found to consist of limonene (27.25%), ocimene (5.55%) and linalool (2.97%). The performance of three available SPME fibers was compared to evaluate the recoveries of volatile compounds in C.grandis flowers and 100 μm polydimethylsiloxane was found to be the most effective.